Empirical Investigation Of Muslim Gen-Z On Revisit Intention Towards Halal Tourism Of Bandung City - Ali Hanafiah; Gian Rafi Firjatullah; Mas Wahyu Wibowo; Indriyani Handyastuti (Jurnal Ilmiah Manajemen dan Bisnis, 2022)
The city of Bandung is the capital of the province of West Java with the majority of the population being Muslim. Currently, Indonesian tourism has a new concept, namely halal tourism. The purpose of this study was to see and analyze the influence of Muslim-friendly amenities, selfie promotion, and service quality on the interest in returning Muslim Generation Z tourists to Halal tourism in Bandung. The object of this research was Generation Z with 147 respondents. The approach used in this study is the Co-variance based Structural Equation Modeling with the Smart-PLS 3.2.8 analysis tool. The results showed that Muslim-friendly communities had a positive and significant influence on the interest in visiting Generation Z Muslims. The results showed that promotional selfies had a positive and significant influence on the interest of Generation Z Muslim visits and service quality had a positive and significant influence on the interest in the return visits of Generation Z Muslims.